A Step-by Step Process in Designing Personalized Reading Content for Slow Learner Children - Marzita Mansor; Wan Adilah Wan Adnan; Natrah Abdullah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
Teaching slow learner children in reading is a challenging process. It requires personalization touch which can deliver suitable reading materials to meet diverse slow learner existing knowledge, needs and preferences. However, despite the various implementation of the personalization in a wide range of areas, the implementation of existing teaching and learning in primary schools in Malaysia does not support personalization. With an intention to cater to slow learner reading difficulties, this research offers a step-by-step process of designing personalization of reading content for slow learner children. In conclusion, developing personalized reading content for the slow learner children is one way of attaining the need for the slow learner children in reading. By offering personalization of reading for the slow learner children, perhaps it would be something interesting tool to be explored by a slow learner to break a code of reading successfully.